In a triangle, the sum of lengths of two sides is x and the product of the lengths of the same two sides is y, If x^{2}−c^{2}=y, where c is the length of the third side of the triangle, then the circumradius of the triangle is 

(a) 
(b) 


(c) 
(d) 
In a triangle, the sum of lengths of two sides is x and the product of the lengths of the same two sides is y, If x^{2}−c^{2}=y, where c is the length of the third side of the triangle, then the circumradius of the triangle is 

(a) 
(b) 


(c) 
(d) 
Given a+b=x and ab=y
If x^{2}−c^{2}=y⇒(a+b)^{2}−c^{2}=ab
⇒
⇒cosC=
⇒ c=
R=